2018
DOI: 10.1002/ardp.201700369
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Bruton's tyrosine kinase for the treatment of B cell associated malignancies and autoimmune diseases: Preclinical and clinical developments of small molecule inhibitors

Abstract: B cell receptor (BCR) signaling plays a key role in B cell development and function. Aberrant BCR signaling has been confirmed as a central driver for the pathogenesis of various B cell malignancies. Bruton's tyrosine kinase (BTK) is a vital component of BCR signaling and exhibits overexpression in various B cell leukemias and lymphomas. Inhibiting BTK has been proved as an efficient way for B cell malignancy intervention. Remarkable achievements have been made in the pursuit of selective BTK inhibitors, repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…We then investigated the antiproliferative activity of compound 2 in TMD8 lymphoma cells, which express high levels of BTK and are widely used to evaluate the antitumor effect of BTK inhibitors [ 18 , 30 32 ]. Ibrutinib and ACP-196 were used as the positive control compounds [ 22 , 33 , 34 ]. The results revealed that compound 2 inhibited the proliferation of TMD8 cells with an IC 50 value of 0.028 μM, indicating that compound 2 was slightly less potent than ibrutinib (IC 50 = 0.010 μM) and ACP-196 (IC 50 = 0.014 μM) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We then investigated the antiproliferative activity of compound 2 in TMD8 lymphoma cells, which express high levels of BTK and are widely used to evaluate the antitumor effect of BTK inhibitors [ 18 , 30 32 ]. Ibrutinib and ACP-196 were used as the positive control compounds [ 22 , 33 , 34 ]. The results revealed that compound 2 inhibited the proliferation of TMD8 cells with an IC 50 value of 0.028 μM, indicating that compound 2 was slightly less potent than ibrutinib (IC 50 = 0.010 μM) and ACP-196 (IC 50 = 0.014 μM) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bruton's tyrosine kinase (BTK) is expressed on B lymphocytes, from pre‐B‐cell to mature B‐cell stages . BTK functions as an important regulator in B‐cell development and as a component of BCR signalling . BTK also promotes mast cell degranulation and cytokine production upon FcεRI cross‐linking .…”
Section: Evolving Therapeutic Targetsmentioning
confidence: 99%
“…BTK inhibition leads to derangements in BCR‐mediated B‐cell pathways, inhibition of neutrophil migration, FcεR‐induced cytokine release from monocytes and macrophages and FcγR‐induced mast cell degranulation . Small molecule BTK inhibitors have been FDA approved for the treatment of mantle cell lymphoma and chronic lymphoblastic leukaemia …”
Section: Evolving Therapeutic Targetsmentioning
confidence: 99%
See 2 more Smart Citations